Learning English as a Foreign Language Writing Skills in Collaborative Settings: A Cognitive Load Perspective - Jiang, Dayu; Kalyuga, Slava (Frontiers in Psychology, 2022)
Learning to write in a foreign language is a complex cognitive process. The interacting elements of procedural knowledge, linguistic knowledge, and generic knowledge in a process-genre approach may exceed the capacity of an individual learner’s working memory. According to collective working memory effect, it was hypothesized that teaching writing skills of English as a foreign language by adopting a process-genre approach in collaborative conditions could lead to better writing performance, lower cognitive load, and higher instructional efficiency. The reported experiment compared learning writing skills of English as a foreign language in individual and collaborative instructional conditions from a cognitive load perspective, a rarely adopted approach in this field. The results indicated that the collaborative instructional condition was more effective and efficient than the individual instructional condition in improving the qualities of written products. Measures of cognitive load were used to support the cognitive load theory’s interpretation of the results.